Nuclear Egress Complexes of HCMV and Other Herpesviruses: Solving the Puzzle of Sequence Coevolution, Conserved Structures and Subfamily-Spanning Binding Properties - Manfred Marschall; Sigrun Häge; Marcus Conrad; Sewar Alkhashrom; Jintawee Kicuntod; Johannes Schweininger; Mark Kriegel; Josephine Lösing; Julia Tillmanns; Frank Neipel; Jutta Eichler; Yves A. Muller; et al. (Viruses, 2020)
Herpesviruses uniquely express two essential nuclear egress-regulating proteins forming a heterodimeric nuclear egress complex (core NEC). These core NECs serve as hexameric lattice-structured platforms for capsid docking and recruit viral and cellular NEC-associated factors that jointly exert nuclear lamina as well as membrane-rearranging functions (multicomponent NEC). The regulation of nuclear egress has been profoundly analyzed for murine and human cytomegaloviruses (CMVs) on a mechanistic basis, followed by the description of core NEC crystal structures, first for HCMV, then HSV-1, PRV and EBV. Interestingly, the highly conserved structural domains of these proteins stand in contrast to a very limited sequence conservation of the key amino acids within core NEC-binding interfaces. Even more surprising, although a high functional consistency was found when regarding the basic role of NECs in nuclear egress, a clear specification was identified regarding the limited, subfamily-spanning binding properties of core NEC pairs and NEC multicomponent proteins. This review summarizes the evolving picture of the relationship between sequence coevolution, structural conservation and properties of NEC interaction, comparing HCMV to α-, β- and γ-herpesviruses. Since NECs represent substantially important elements of herpesviral replication that are considered as drug-accessible targets, their putative translational use for antiviral strategies is discussed.